B‐type natriuretic peptide measurement for early diagnosis of acute pulmonary edema during pregnancy. (17th September 2014) - Seror, Jeremy; Lefevre, Guillaume; Berkane, Nathalie; Richard, Frederic; Bornes, Marie; Uzan, Serge; Berkane, Nadia
Abstract Calcium‐channel blockers administered to pregnant women as tocolytic agents can cause acute pulmonary edema. The first signs of this severe complication can be atypical and so delay introduction of appropriate therapy. We describe three cases in whom B‐type natriuretic peptide measurements proved to be relevant in early diagnosis and monitoring of pregnant women with acute pulmonary edema. B‐type natriuretic peptide measurement in this setting could contribute to timely diagnosis and improve follow‐up.